1994
DOI: 10.1088/0953-4075/27/14/049
|View full text |Cite
|
Sign up to set email alerts
|

On the local theory of resonant inelastic collisions of slow electrons with carbon dioxide

Abstract: A method of calculating the cross sections of inelastic vibronic transitions in collisions of slow electrons with polyatomic molecules in the framework of the local theory (the 'boomerang' model) is proposed. The method is based on the study of the time evolution of the initial vibronic wavefunction; the evolution is governed by the (complex valued) Hamiltonian of the intermediate anion state. The method has been applied to the consideration of inelastic electron collisions with the CO2 molecule in the two-mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 36 publications
(24 reference statements)
1
23
0
Order By: Relevance
“…The results, obtained in [6], have demonstrated that the additional quenching of the one-dimensional 'boomerang' state (which was discussed in [7,8]) arises what was attributed to the wave packet sliding from the 'ridge' of the linear configuration of the intermediate anion. Presently we develop the improved one-dimensional approach which shows definitely that the sliding indeed plays a significant role in the dynamics of the process.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…The results, obtained in [6], have demonstrated that the additional quenching of the one-dimensional 'boomerang' state (which was discussed in [7,8]) arises what was attributed to the wave packet sliding from the 'ridge' of the linear configuration of the intermediate anion. Presently we develop the improved one-dimensional approach which shows definitely that the sliding indeed plays a significant role in the dynamics of the process.…”
Section: Introductionmentioning
confidence: 88%
“…In this section we reiterate the essential notations as they were given in our previous publication [6].…”
Section: Description Of the 'Boomerang' Modelmentioning
confidence: 99%
See 3 more Smart Citations